Case report: Otitis media with subsequent mastoiditis and cerebral herniation in a patient with Arnold chiari malformation - Feussner, Oskar; Haase, Roland; Baier, Jan (Frontiers in Pediatrics, 2023)
We present the case of a 13-year-old boy who unexpectedly needed to be resuscitated at home after an assumed uncomplicated otitis media. Imaging at our clinic showed mastoiditis and a cystoid mass in the left cerebellopontine angle compressing the brainstem, as well as an Arnold-Chiari-Malformation. Both the laboratory examination of cerebrospinal fluid (CSF) and surgical biopsy with pathological evaluation of the mastoid supported the inflammatory etiology of the mass. Microbiologically, Streptococcus intermedius was detected in the blood culture and CSF. Due to brain death, which most likely already existed preclinically, the organs were released for donation during the course. Our case demonstrates a very rare lethal complication of acute otitis media on the basis of a cerebral malformation and emphasizes the need to stay alert when patients complain of symptoms after assumed resolution.